2012
DOI: 10.1186/1471-2334-12-38
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of bone markers, parathormone and 1,25-(OH)2 vitamin D in HIV-positive patients after the initiation of tenofovir/emtricitabine with atazanavir/ritonavir or efavirenz

Abstract: BackgroundIncreased risk of fractures and osteoporosis have been associated with the use of antiretroviral drugs. There is a paucity of prospective evaluations of bone markers after the initiation of drugs currently recommended to treat HIV infection and results on the evolution of these markers are conflicting. Lastly, the effect of tenofovir on 1,25-(OH)2 vitamin D is uncertain.MethodsWe performed a prospective study on the evolution of bone markers, parathormone and 1,25-(OH)2 vitamin D before and after sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
2
26
2
Order By: Relevance
“…6,28 Initiation of ART increases bone turnover: TDF-containing regimens lead to greater changes in bone turnover markers and greater BMD declines than regimens without TDF. 23,24,[29][30][31][32][33] In this study, declines in hip and spine BMD over 48 weeks were smaller in the TAF group than in the TDF group; the BMD findings were supported by significantly less change in markers of bone turnover in the TAF group. The magnitude of BMD declines in the TAF group is among the lowest seen when naive participants have been evaluated by dual-energy x-ray absorptiometry.…”
Section: Discussioncontrasting
confidence: 34%
“…6,28 Initiation of ART increases bone turnover: TDF-containing regimens lead to greater changes in bone turnover markers and greater BMD declines than regimens without TDF. 23,24,[29][30][31][32][33] In this study, declines in hip and spine BMD over 48 weeks were smaller in the TAF group than in the TDF group; the BMD findings were supported by significantly less change in markers of bone turnover in the TAF group. The magnitude of BMD declines in the TAF group is among the lowest seen when naive participants have been evaluated by dual-energy x-ray absorptiometry.…”
Section: Discussioncontrasting
confidence: 34%
“…The authors observed an increase in key osteoclast stimulating inflammatory cytokines [tumor necrosis factor-alpha (TNF-α) and receptor activator of nuclear factor kappa-B ligand (RANKL)] and hypothesized that inflammation driven largely by reconstituting T cells may be responsible for the observed increase in bone resorption [33]. However, the sample size of this study was limited and other studies have also reported decreases in TNF-α and RANKL levels after initiation of ART regimens with and without TDF [9,34]. Therefore further research is necessary to fully understand how these inter-related mechanisms of renal dysfunction, alterations in DBP and vitamin D metabolism, and the changing inflammatory and immunologic milieu intersect in TDF-associated bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Tenofovir disoproxil fumarate (TDF) has been consistently associated with a 1–2% greater decline in BMD compared to other nucleoside reverse transcriptase inhibitors when used in combination with other ARTs [6,1416]. The mechanism of TDF’s effect on the skeleton remains uncertain, and may be related to direct effects on bone cells, or indirect effects due to secondary hyperparathyroidism and disruption of calcium-phosphate homeostasis resulting in inadequate bone mineralization [17–20]. Protease inhibitor (PI)-containing regimens have been shown to be associated with greater bone loss than non-PI containing regimens in some [16,21,22] but not all studies [8].…”
Section: Introductionmentioning
confidence: 99%